Exploring demographic influences on students' academic performance over a five-year programme - Sommerville, T.; Singaram, V.S. (South African Journal of Higher Education, 2018)
Introduction: This mixed-method interpretive study examines the influence of five demographic characteristics or factors on the academic achievements of a cohort of 202 students through a five-year medical degree programme. Methodology: A quantitative analysis was performed, analysing a series of 32 summative assessments according to racial grouping (as defined in South Africa), first language, sex, age at entry, and source of finance for study. During the cohort’s third year, a stratified sample of 19 students and six staff members was interviewed, individually or in groups. Their opinions on these five factors were elicited using, as stimuli for discussion, graphs showing the performance of a previous cohort. Results: Quantitative analysis of assessment marks demonstrated statistical differences between groups of students when examined according to race, first language, or financial support, the differences being maintained over the full five years. No significant differences were seen according to sex or age. Qualitative investigation revealed a number of opinions on, and explanations of, the differences observed. Some respondents’ comments and proposed explanations seemed, at first, counterintuitive, yet appropriate to the pertaining circumstances. Conclusions: This study has implications for academic development, and advances the literature on diversity and demographic factors influencing student achievement, beyond mere statistics by exploring the details of students’ lives as they relate to the factors investigated.